Ultrasound guided fine needle aspiration cytology of gall bladder mass and mural thickening: a radio-pathological correlation - Barman, Geetanjali; Bujarbaruah, Kabita; Choudhury, Binoy Kumar; Ahmed, Shiraj; Sharma, Jagannath Dev; Kataki, Amal Chandra (International Journal of Research in Medical Sciences, 2019)
Background: Carcinoma of the gall bladder (GB) is the commonest malignancy of the biliary tract. Ultrasound (US) guided Fine Needle Aspiration Cytology (FNAC) plays a major role in early detection of malignancy in a suspicious GB lesion. The aim of this study was to evaluate the safety and diagnostic accuracy of US guided FNAC in detection of GB malignancy, to find the association of gall stones with GB malignancy, to study the ultrasound pattern of GB malignant mass and demographic profile of the disease in North eastern India. Methods: The study was conducted retrospectively in Dr. B. Borooah Cancer Institute, Guwahati from January 2016 to December 2017. A total number of 173 patients suspected to have GB malignancy were subjected to US guided FNAC. Results: Total 161 patients were positive for malignancy with significant female majority. There were 124 female (77.02%) and 37 males (22.98%) in the range of 29 to 82 years. Male female ratio was 1:3.5. One was diagnosed as xanthogranulomatous cholecystitis and another was chronic cholecystitis. FNAC remained inconclusive in 2 patients. There was no major procedure related complication. Adenocarcinoma was the most common malignancy found in 146 patients (98.68%). Cholelithiasis was associated in 88.19% of malignant lesions. Conclusions: US-guided FNAC is a safe, highly accurate and reliable procedure for early detection of GB malignancy.